Labuan limited partnership and limited liability partnerships Act 2010: an appraisal - Abd Ghadas, Zuhairah Ariff (2010)
In Malaysia, the business vehicles are merely confined to sole proprietorships, partnerships and company. However, in its offshore, Labuan, there are additional business vehicles which are offered, namely limited partnerships (LP) and limited liability partnerships (LLP). Recently, Labuan regulatory centre, LFSA came out with a new and unimitable statute known as Labuan Limited and Limited Liability Partnerships Act 2010 which is a unique legislation as it combines the laws for two business vehicle; limited partnership (LP) and limited liability partnerships (LLP) under one statute. In other countries, the limited partnerships and limited liability partnerships are regulated under different statutes as they are different both in substance and in practice. This paper intends to discuss the main features of Labuan Limited Partnership and Limited Liability Partnership Act 2009 and to highlight the distinctiveness of this new business law. Research methodology adopted for this paper is mainly statutory analysis.